The first repeated absolute gravity measurement for geothermal monitoring in The Kamojang Geothermal Field, Indonesia. (January 2015) - Sofyan, Yayan; Daud, Yunus; Nishijima, Jun; Fujimitsu, Yasuhiro; Kamah, Yustin; Yani, Ahmad; Fukuda, Yoichi; Taniguchi, Makoto
Highlights: The KGF is a geothermal field with the longest history of utilization in Indonesia. Introduces new technology for geothermal monitoring using absolute gravimeter. Evaluates previous gravity monitoring of relative gravity measurement at KGF. Provide precise gravity change data to clarify mass variation in the subsurface. The absolute measurements at KGF provide good base lines for future monitoring. Abstract: In more than 25 years, repeated gravity measurements (RGM) for geothermal monitoring have been applied in the Kamojang Geothermal Field (KGF), Indonesia. Pertamina has carried out RGM using relative gravimeters at more than 50 benchmarks at KGF since 1984. They used LaCoste-Romberg type G 653, G 655, and Scintrex CG-3 gravimeters to estimate gravity variation. In 2009, we introduced a new microgravity network using A10 (#017) micro-g, a portable absolute gravimeter, which we re-occupied in 2010 and 2011. We identify gravity value changes in production and injection area of KGF as well as changes at the reference station. A linear trend of declining mass of about −17.9 μGal/year at PG48A, a benchmark far from production and injection wells, reveal the temporal gravity variation outside of geothermal reservoirs. The series of monitoring in this present research shows the distribution of large negative gravity changes up to −80 μGal. The large mass loss stays continues to maintain massive production throughout 200 MWe installed capacities at KGF. The absolute gravity measurements improve the result of gravity change data for monitoring. This present study introduces new technology that will enhance the method of reservoir monitoring using repeated precisely-gravity measurements. The use of absolute gravimeter is the best way to account for regional effect, and correct for changes at the base and reference station over time.